2023
DOI: 10.1371/journal.pgph.0001214
|View full text |Cite
|
Sign up to set email alerts
|

Gender equality related to gender differences in life expectancy across the globe gender equality and life expectancy

Abstract: Life expectancy (LE) depends on the wider determinants of health, many of which have gendered effects worldwide. Therefore, this study aimed to investigate whether gender equality was associated with LE for women and men and the gender gap in LE across the globe. Gender equality in 156 countries was estimated using a modified global gender gap index (mGGGI), based on the index developed by the World Economic Forum between 2010 and 2021. Linear regression was used to investigate the association between the mGGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…14 The GGGI has been used as an indicator to predict gender disparities in medicine since it benchmarks 146 countries with a higher ranking meaning a higher level of gender parity in a country. 15,16…”
mentioning
confidence: 99%
“…14 The GGGI has been used as an indicator to predict gender disparities in medicine since it benchmarks 146 countries with a higher ranking meaning a higher level of gender parity in a country. 15,16…”
mentioning
confidence: 99%
“… Vyas-Doorgapersad (2019) reached the conclusion that gender equality was a significant instrument to combat poverty in South Africa. Pinho-Gomes et al (2023) analyzed the relationship between gender equality and gender differences in life expectancy in 156 countries over the 2010–2021 period through regression analysis and revealed that higher gender equality was related to longer life expectance for women and men, but that the gender gap in life expectancy had widened. Kolip and Lange (2018) found a similar interaction between gender inequality and the gender gap in life expectancy for the European Union member states.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cтандартизированная по возрасту распространенность диабета среди взрослых, по меньшей мере, удвоилась среди мужчин в 120 странах и среди женщин в 87 странах [7]. В странах с высоким уровнем дохода в 2020 году от самоубийств умерло в три раза больше мужчин, чем женщин, в то время как во всем мире соответствующий показатель был почти в два раза больше [8]. Аналогичная картина наблюдается и в дорожно-транспортных происшествиях: почти три четверти (73%) всех смертей в результате дорожно-транспортных происшествий приходится на молодых мужчин в возрасте до 25 лет [8,9].…”
unclassified
“…В странах с высоким уровнем дохода в 2020 году от самоубийств умерло в три раза больше мужчин, чем женщин, в то время как во всем мире соответствующий показатель был почти в два раза больше [8]. Аналогичная картина наблюдается и в дорожно-транспортных происшествиях: почти три четверти (73%) всех смертей в результате дорожно-транспортных происшествий приходится на молодых мужчин в возрасте до 25 лет [8,9]. На многие проблемы со здоровьем, с которыми сталкиваются мужчины, заметно влияют социальные детерминанты здоровья и межсекторальные факторы, при этом социально-экономическое давление, этническая принадлежность, инвалидность, а также пол и статус сексуального меньшинства -все это связано с повышенным риском неравенства в отношении здоровья [10][11][12][13].…”
unclassified